Motivasi sebagai Kunci Peran dalam Pendidikan - Habsy, Bakhrudin All; Santoso, Hikmal Ramdhan Priyo; Nurfirda, Ida; Putri, Cindy Kartika (Lembaga Yasin AlSys, 2024)
Motivation is one of the key factors that influences human behavior in various life contexts. Motivation is an important factor in motivating students to learn and achieve academic success. Motivation is the main driver behind academic achievement and student development. Motivation itself is divided into two factors, namely external and internal. External motivation is motivation that comes from outside. Usually includes the family, school and surrounding environment, both social and non-social environments. while internal motivation is motivation that comes from within the student. Usually includes integrity, self-confidence and desire to achieve something. The aim of this research is to find out about the factors that influence student learning motivation and the role of motivation in learning as well as how to increase and maintain student motivation. The research method used is a literature review (Library Research) located in the library/reading room online and offline. The research data source used is a primary source. Motivation is the main factor in learning, namely its function is to give rise to, underlie and drive the act of learning. From this research, it can be found that there are several factors that influence student learning motivation and the role of motivation in learning as well as ways that can be done to increase and maintain student motivation.